ANALISIS PERKUATAN LERENG MENGGUNAKAN GEOGRID YANG DIPERKUAT DENGAN RIGID INCLUSION DAN BORED PILE - Pahlawan, Cakra Wicaksana; Suhendra, Andryan (JMTS: Jurnal Mitra Teknik Sipil, 2024)
Reinforced Slope Structure is a strengthening structure made on a slope using additional materials, usually using geogrid to increase the slope stability value. Geogrid is a polymer material that has strong elastic properties and is resistant to certain tensile forces. In this research, Reinforced Slope Structure modeling was carried out combined with Rigid Inclusion and Bored Pile as local soil reinforcement. In the Reinforced Slope Structure modeling, internal and external stability values ​​were analyzed and variations in pseudostatic wave strength were carried out. Based on the analysis results, a safety factor value is obtained which refers to a standard. For the analysis of pseudostatic wave strength, it is assisted by the finite element method program, so that researchers can draw conclusions regarding the use of Reinforced Slope Structure on this slope embankment. Therefore, in this research, modeling of an earth embankment with a height of 14.56 meters was carried out to obtain the overturning safety factor value of 13.233, a sliding safety factor of 2.35, a static global safety factor of 1.506, and a dynamic global safety factor with different earthquake coefficient values. assisted using 2D finite element applications. Abstrak Reinforced Slope Structure merupakan suatu struktur perkuatan yang dibuat pada lereng dengan menggunakan material tambahan, biasanya menggunakan geogrid untuk meningkatkan nilai stabilitas lereng. Geogrid merupakan bahan bermaterial polimer yang memiliki sifat elastis yang kuat dan tahan terhadap gaya tarik tertentu. Pada penelitian ini, dilakukan permodelan Struktur Reinforced Slope Structure yang dikombinasikan dengan Rigid Inclusion dan Bored Pile sebagai perkuatan tanah setempat. Pada permodelan Reinforced Slope Structure dilakukan analisis nilai stabilitas internal, eksternal, dan dilakukan analisis terhadap variasi kuat gelombang pseudostatic. Berdasarkan hasil analisis didapatkan suatu nilai faktor keamanan yang mengacu pada suatu standar. Untuk analisis kuat gelombang pseudostatic dibantu dengan program metode finite element, sehingga peneliti dapat membuat kesimpulan terhadap penggunaan Reinforced Slope Structure pada timbunan lereng ini. Oleh karena itu, pada penelitian ini dilakukan permodelan timbunan tanah dengan tinggi 14,53 meter didapatkan nilai faktor keamanan guling sebesar 13,233, faktor keamanan geser sebesar 2,35, faktor keamanan global statik sebesar 1,506, serta faktor keamanan global dinamik dengan nilai koefisien gempa yang berbeda-beda yang dibantu menggunakan aplikasi finite element 2D.